1983
DOI: 10.1002/pol.1983.180210815
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of local flow effects in flow‐induced orientation and crystallization

Abstract: SynopsisAn analysis is presented of the effects of external flow kinematics on the so-called local flow in seeded, flow-induced crystallization and orientation. The flow field around a growing crystal or nucleation seed is modelled by the Stokes flow equations past a prolate ellipsoid of high aspect ratio. Exact solutions for various flow kinematics, worked out elsewhere by the singularity method, are applied here to the analysis of local gradients. The results show that along the symmetry axis of the spheroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The three terms on the right hand side represent respective contributions to the macroscopic flow due to a uniform free stream flow, a planar extensional flow, and a stagnation-like quadratic extensional flow. Chwang and Wu [11] and Chwang [12] have obtained complete closed form solutions to the Stokes flow equations for the local flow past a prolate spheroid immersed in such unbounded free stream flows (see also [8]). Their integral expressions can be evaluated analytically in the region near the spheroid symmetry axis, leading to the following results for the dimensiona ~b / x less local stretch rate, 9-= V1 ~x ' along the spheroid symmetry axis (y = 0) for each of the indicated free stream flow fields.…”
Section: Analysis Of the Macroscopic And Local Flow Fieldsmentioning
confidence: 97%
See 3 more Smart Citations
“…The three terms on the right hand side represent respective contributions to the macroscopic flow due to a uniform free stream flow, a planar extensional flow, and a stagnation-like quadratic extensional flow. Chwang and Wu [11] and Chwang [12] have obtained complete closed form solutions to the Stokes flow equations for the local flow past a prolate spheroid immersed in such unbounded free stream flows (see also [8]). Their integral expressions can be evaluated analytically in the region near the spheroid symmetry axis, leading to the following results for the dimensiona ~b / x less local stretch rate, 9-= V1 ~x ' along the spheroid symmetry axis (y = 0) for each of the indicated free stream flow fields.…”
Section: Analysis Of the Macroscopic And Local Flow Fieldsmentioning
confidence: 97%
“…We have found that running at a die temperature of 140 °C allows crystallization to occur at the seed tip and direct visualization of the phase transformation has been possible by observing the process through optical windows under normal and polarized light. Following the method discussed by Dairanieh and McHugh [8], a mathematical analysis of the local flow in the vicinity of the needle has also been carried out for the geometry used in this experiment and is presented.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evolution of microdiffraction patterns of shear crystallized polyethylene specimens with shear rate from spherulitic through complex patterns toward scattering from oriented fibrils; vertical shear direction [47] strain-induced crystallization [50,51], while the structure formation is more temperature sensitive.…”
Section: Formation Of Macrofibrils In Shear Crystallizationmentioning
confidence: 99%